Efficient Tuning-Free l1-Regression of Nonnegative Compressible Signals - Petersen, Hendrik Bernd; Bah, Bubacarr; Jung, Peter (Frontiers in Applied Mathematics and Statistics, 2021)
In compressed sensing the goal is to recover a signal from as few as possible noisy, linear measurements with the general assumption that the signal has only a few non-zero entries. The recovery can be performed by multiple different decoders, however most of them rely on some tuning. Given an estimate for the noise level a common convex approach to recover the signal is basis pursuit denoising. If the measurement matrix has the robust null space property with respect to the l2-norm, basis pursuit denoising obeys stable and robust recovery guarantees. In the case of unknown noise levels, nonnegative least squares recovers non-negative signals if the measurement matrix fulfills an additional property (sometimes called the M+-criterion). However, if the measurement matrix is the biadjacency matrix of a random left regular bipartite graph it obeys with a high probability the null space property with respect to the l1-norm with optimal parameters. Therefore, we discuss non-negative least absolute deviation (NNLAD). For these measurement matrices, we prove a uniform, stable and robust recovery guarantee without the need for tuning. Such guarantees are important, since binary expander matrices are sparse and thus allow for fast sketching and recovery. We will further present a method to solve the NNLAD numerically and show that this is comparable to state of the art methods. Lastly, we explain how the NNLAD can be used for viral detection in the recent COVID-19 crisis.